Secure ACO-Based Wireless Sensor Network Routing Algorithm for IoT - Sharmin, Afsah; Anwar, Farhat; Motakabber, S. M. A.; Hassan Abdalla Hashim, Aisha (IEEE, 2021)
The problem of developing effective and secure routing protocols has drawn more interest in network research with the popularization of IoT-connected devices. The perception of ensuring security is expensive in terms of computation, power and user-interface components because of low-power IoT objects or sensor nodes. Secret keys distribution schemes are computationally expensive and require more resources. Rather, bio-inspired mechanisms are considered more robust as they offer optimal and inexpensive solutions for designing secure routing algorithms for their inherent adaptable and scalable features. Moreover, trusted neighbor discovery is a crucial task. That is why a complementary security measure, trust evaluation system, is adopted here. In this paper, a secure bio-inspired WSN (Wireless Sensor Network) routing protocol based on ant colony optimization (ACO) algorithm for IoT has been proposed and analyzed to find secure and optimal path that is energy-efficient as well as aiming at providing trust in IoT environment. The performance of the proposed routing algorithm is evaluated utilizing MATLAB. The assessment results indicate that it can find the forwarding path with comparatively low cost in the premise of ensuring security and has minimized the average energy consumption by nearly 50% even as the number of nodes has increased, when compared with the traditional ACO algorithm, an existing ant colony based routing algorithm and a current routing protocol for IoT.